Komformitas Perilaku Membolos Siswa Di Sekolah Tingkat Sma/Smk - Habib, Farhan Ramadhan (Fakultas Pendidikan Ilmu Keguruan, Universitas Pahlawan Tuanku Tambusai, 2024)
Skipping school is a real manifestation of deviant behavior in children, especially in the realm of juvenile delinquency. This research aims to assess the extent to which high school and vocational school students are involved in truant behavior, using a qualitative research approach with data collection methods rooted in library research. Research findings show that many factors contribute to student absenteeism, both external and internal in the school environment. External factors include a lack of support at home for academic focus and an unstable family economy. Other external factors involved the existence of confrontational dynamics between students and teachers, while the security measures implemented by schools to handle and monitor truancy were found to be inadequate, and peer influence played a significant role. Internally, the decision to skip classes is driven by psychological factors such as fear of punishment and guilt, forcing students to choose not to attend. In summary, this research highlights the complex interactions between internal and external factors that influence students’ decisions to skip school.